2016
DOI: 10.18488/journal.aefr/2016.6.5/102.5.247.260
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Housing Prices in an Oil Based Economy

Abstract: This paper is trying to analyze the determinants of housing prices in an oil-based economy, where the price of oil plays a major role in such economies. It is also common to find that government spending represents the most important component of aggregate spending and that governments usually play a central role in the provision of public services to citizens at substantial subsidies, housing is on top of them. The paper is trying to identify the role played by oil price in the housing market in Kuwait. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Real estate are used by individuals during inflation. The inflation rate has direct influence on real estate price (Almutairi, 2016). As earlier anticipated, high inflation rates raises the real estate price, the higher rate of inflation, the price of real estate will be higher, of course the response of real estate prices to inflation rates may depend on numerous factors that include real estate supply, intensity of demand and market condition (Almutairi, 2016).…”
Section: Relationship Between Real Estate Price and Inflation Ratementioning
confidence: 97%
See 3 more Smart Citations
“…Real estate are used by individuals during inflation. The inflation rate has direct influence on real estate price (Almutairi, 2016). As earlier anticipated, high inflation rates raises the real estate price, the higher rate of inflation, the price of real estate will be higher, of course the response of real estate prices to inflation rates may depend on numerous factors that include real estate supply, intensity of demand and market condition (Almutairi, 2016).…”
Section: Relationship Between Real Estate Price and Inflation Ratementioning
confidence: 97%
“…Therefore, if the interest rate increases, the cost of real estate investment will also increases and some real estate investors will reduce their investment scale, which will decrease the supply of real estate and increase the price (Zhang et al 2016). Moreover, higher rate of interest has some consequences on the prices, where interest rate increase will have negative impact on the demand for housing, as the housing demand will be lower and it affects the direction of house prices (Almutairi, 2016…”
Section: Relationship Between Real Estate Price and Interest Ratementioning
confidence: 99%
See 2 more Smart Citations
“…Findings of the research indicate that among all factors, only land supply has a significant effect on the real estate prices. Almutairi and El-Sakka (2016) analyzed housing affordability as well as main price determinants of real estate in Kuwait. Authors concluded that government’s incompetence in housing provision is the reason of an acute housing affordability problem which in turn ignites property prices.…”
Section: Literature Reviewmentioning
confidence: 99%